Heat synchronization with Alfaprostol - Keay, L.E.; Kiracofe, G.; Odde, Kenneth G.; Stevenson, Jeffrey S. (Kansas State University. Agricultural Experiment Station, 2010)
One-hundred eighteen heifers were used to determine the effectiveness of Alfaprostol as a heat synchronization agent. Seventy-nine were injected twice (12 days apart) with 6 mg Alfaprostol per head and 39 were not treated. Twelve to 96 hours after the second injection 88.6% of the treated heifers were in standing heat and 81.4% of those in heat conceived at the first insemination. Eighty-one percent of the 37 untreated heifers in heat the first 21 days conceived at the first insemination. Ninety-one percent of the treated heifers and 89.2% of the untreated heifers conceived within a 50-day breeding period, so Alfaprostol did not affect reproductive performance.
Keywords: Beef; Alfaprostol; Heat synchronization; Reproductive performance